2005
DOI: 10.1385/endo:27:3:301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Troglitazone on the Excess Testosterone and LH Secretion in Thyroidectomized, Insulin-Resistant, Type 2 Diabetic Goto–Kakizaki Rats

Abstract: Our previous study suggested that hypothyroidism in Goto-Kakizaki (GK) rats with insulin resistance and type 2 diabetes elevates their serum testosterone and luteinizing hormone (LH) levels and ovarian LH receptor messenger RNA (mRNA) expression. The present study assessed the effects of troglitazone (Tro), an insulin-sensitizing agent, on these hypothyroidism-induced hormonal changes in GK rats. GK and normal (Wistar strain) female rats were thyroidectomized (Tx) and then injected with 5 IU of equine chorioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Experimental and clinical studies showed that this imbalance in sex hormone levels in men with type 1 diabetes (18,35) and male streptozotocin (STZ)-induced diabetic rats (18,35) is associated with the progression of diabetic renal disease. Similar to males, diabetic females also exhibit an imbalance in sex hormone levels, albeit in the opposite direction: decreased estradiol and increased testosterone levels (19,27). The changes in the balance in sex hormone levels in both males and females support that concept that sex hormones may play a role in the pathogenesis of diabetic renal disease.…”
mentioning
confidence: 54%
“…Experimental and clinical studies showed that this imbalance in sex hormone levels in men with type 1 diabetes (18,35) and male streptozotocin (STZ)-induced diabetic rats (18,35) is associated with the progression of diabetic renal disease. Similar to males, diabetic females also exhibit an imbalance in sex hormone levels, albeit in the opposite direction: decreased estradiol and increased testosterone levels (19,27). The changes in the balance in sex hormone levels in both males and females support that concept that sex hormones may play a role in the pathogenesis of diabetic renal disease.…”
mentioning
confidence: 54%
“…Specifically, men have low testosterone and high estradiol levels [74][75][76] in contrast to women who exhibit low estradiol and higher testosterone levels. 77,78 An imbalance in sex hormone levels as well as differential expression of renal estrogen and androgen receptors by sex has been reported in experimental models of DKD. [79][80][81] Several studies have also suggested that restoring the sex hormone imbalance may be an effective treatment for DKD.…”
Section: Contribution Of Sex Hormones To Dkdmentioning
confidence: 99%
“…Although there are reports about the effects of hypothyroidism in the type 1 (Hibbe et al, 1991) and type 2 diabetic models (Matsushita et al, 2005; Tamura et al, 2005; Hwang et al, 2009), no studies have been reported about the effects of hypothyroidism in type 2 diabetic model on cell proliferation and neuroblast differentiation. In the present study, we investigated the consequences of adult-onset hypothyroidism in diabetic rats using methimazole, an anti-thyroid drug, which has been used in the management of hyperthyroid patients (Cooper 2005).…”
Section: Introductionmentioning
confidence: 99%